1998
DOI: 10.1161/01.str.29.6.1209
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inducible Nitric Oxide Synthase and Cyclooxygenase-2 in Endotoxin-Induced Cerebral Hyperemia

Abstract: Background and Purpose-Bacterial lipopolysaccharide (LPS), an endotoxin, has been reported to induce the expression of inducible isoforms of both nitric oxide synthase (iNOS) and cyclooxygenase (COX-2) in various cell types. LPS is also known to dilate systemic vasculature, including cerebral vessels. This study aimed to determine to what extent LPS induces iNOS and COX-2 expression in the brain and whether NO and/or cyclooxygenase metabolites derived from iNOS and/or COX-2 contribute to the LPS-induced cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
54
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 65 publications
5
54
0
4
Order By: Relevance
“…The NO produced in endothelial cells activates COX to produce more eicosanoids (129,130). In many models of inflammation, there is a concommitant induction of both NOS-2 and COX-2, such as after intracerebroventricular injections of lipopolysaccharide (131) or cerebral ischemia (132), and the NO produced influences the COX-2 activity. NO also facilitates the induction of COX-2 by IL-1 (133).…”
Section: No /Cox Interactionsmentioning
confidence: 99%
“…The NO produced in endothelial cells activates COX to produce more eicosanoids (129,130). In many models of inflammation, there is a concommitant induction of both NOS-2 and COX-2, such as after intracerebroventricular injections of lipopolysaccharide (131) or cerebral ischemia (132), and the NO produced influences the COX-2 activity. NO also facilitates the induction of COX-2 by IL-1 (133).…”
Section: No /Cox Interactionsmentioning
confidence: 99%
“…In the present study, we did not measure body temperature in the rat pups, because this is extremely difficult to do in such small animals. However, in experiments on adult animals, fever has not been reported after intracerebroventricular administration of LPS (19,20). The experimental protocols were approved by the appropriate institutional review committee and met the guidelines of the governmental agency responsible.…”
Section: Animalsmentioning
confidence: 99%
“…Interestingly, PGE 2 was shown to synergize with NO in mediating LPS-induced cerebral hyperemia (14), whereas the vasoconstrictor thromboxane antagonizes NO-mediated vasodilation (15). Several in vitro reports have suggested that NO activates COX activity, but these observations are still controversial, and in vivo data are scarce (for a recent review, see Ref.…”
mentioning
confidence: 99%